Human Rights Education and Religious Education: Design-based Research on Integrating HRE into RE Teacher Education - Trefzer, Franziska; Pirner, Manfred (Journal of Empirical Theology, 2023)
This paper explicates the conceptual background, design and first results of the empirical research project "The Rights of the Child and the School Subject of Religious Education"that aims to integrate children's rights into RE as well as into RE teacher education with a design-based research (DBR) approach. It starts by claiming a central significance of human rights for humanity and social cohesion in society and the world and therefore also for school education. It continues to clarify the relationship between human rights values and religious values and argues for a special potential and obligation of RE for promoting human rights and children's rights - which is to date only partly fulfilled in German RE. Building upon this, the sub-project "Human Rights Education for Religious Educators"(HRE4RE) is introduced. This research demonstrates that it is necessary to establish human rights and children's rights education for student teachers of RE, in order for them to be able to adequately integrate children's rights perspectives into school culture as well as into RE for generations to come.
CRIS-Team Scopus Importer:2023-10-06
Keywords: children's rights; design-based research; human rights education; RE teacher education; religious education

Menschen- und Kinderrechte als Leitnormen schulischer Wertebildung. Grundlagen und Konzeption eines Seminarangebots für Lehramtsstudierende - Pirner, Manfred; Trefzer, Franziska (Wertebildung im Lehramtsstudium – Beiträge aus Wissenschaft, Forschung und Schulpraxis, 2024)

Reisen in Lernlandschaften. Die „Nürnberger Lernumgebung Religionsdidaktik: Schöpfung“. Empirische Einblicke – (Religions)Didaktische Ausblicke - Bedruna, Verena; Haußmann, Werner; Trefzer, Franziska (Spielen, Lernen, Arbeiten in Lernwerkstätten. Facetten der Kooperation und Kollaboration, 2020)